If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 45 + 65x = 50 Solving 45 + 65x = 50 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-45' to each side of the equation. 45 + -45 + 65x = 50 + -45 Combine like terms: 45 + -45 = 0 0 + 65x = 50 + -45 65x = 50 + -45 Combine like terms: 50 + -45 = 5 65x = 5 Divide each side by '65'. x = 0.07692307692 Simplifying x = 0.07692307692
| 4x^2-27x+29=-3x+2 | | 44x+1=45 | | 2.25x+3=4.125 | | 25%d=4 | | 150m-75m+56375=52250-200m | | 3v+12=45 | | n+6(2)-9=23 | | 2e=e | | 4x^2+8x=O | | -2x^2-2x+24.01=0 | | -11x-9=68 | | 7x+8x-76=38-4x | | x-.3x=6000 | | 3x-33=20 | | 8x-4x+120=8x+68 | | x+(x*2)=84 | | 9x-(4x-4)=29 | | 9(d-3)+5= | | 5x-5(x+11)=180 | | 4v-82=81 | | ln(30)= | | 4(x-2)=5x-9-x | | X^2+2.5x^2=36 | | -2x^2-2x+25.99=0 | | 8x-4x+112=8x+60 | | (6i)(-2-3i)= | | 10x-10=9x+1 | | -3r=-15 | | 6x+8=4(x+6) | | -2x^2-2x+26.01=0 | | 5g^2+40g+35=0 | | 6(x-3)+2=3x+3(-4+x) |